1973
DOI: 10.1080/00288306.1973.10431374
|View full text |Cite
|
Sign up to set email alerts
|

Named tephras and tephra formations occurring in the Central North Island, with notes on derived soils and buried paleosols

Abstract: Published names of tephra formations and members are arranged in chronological order, with estimated ages, distribution, and a statement of their mineralogical composition. The clay minerals in surface soils and in buried paleosols derived from them are listed, and the surface soils are classified.The sources of the tephras are mapped, with the 30 em isopachs of tephras that occur within 45 em of the surface and the 15 em isopachs of tephras found between 45 and 100 em from the surface also shown.The sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1976
1976
1994
1994

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Pullar (1967), describing a profile near Tirau, suggested that Tirau Ash comprised Taupo Pumice and the Rotorua and Rotoma Ashes. The ages of these tephra (Pullar et al 1973) are younger than the Egmont Ash, which suggests that Mairoa Ash would underlie Tiran Ash. Alternatively the two deposits may interdigitate or be indistinguishable.…”
Section: Tirau and Mairoa Ashes-previous \X'orkmentioning
confidence: 99%
“…Pullar (1967), describing a profile near Tirau, suggested that Tirau Ash comprised Taupo Pumice and the Rotorua and Rotoma Ashes. The ages of these tephra (Pullar et al 1973) are younger than the Egmont Ash, which suggests that Mairoa Ash would underlie Tiran Ash. Alternatively the two deposits may interdigitate or be indistinguishable.…”
Section: Tirau and Mairoa Ashes-previous \X'orkmentioning
confidence: 99%
“…1), c. 1000 yrs B.P. (Pullar et al 1973) was found in any of the cores examined. This confirms the strong westerly fallout pattern of this tephra (Gibbs 1968;Pullar et al 1973).…”
Section: ) Okareka and Rotorua Ashes Have Betweenmentioning
confidence: 99%
“…The maximum age ot the Hinuera Formation is presently uncertain, although Hume et al (1975) suggested Hinuera-l aggradation may have commenced following emplacement of the ash-flow deposits and tephra.~ of the Rotoiti Breccia Formation in the Central Volcanic Region of the North Island, erupted between about 45000 and 40000 yr BP (Pullar et al 1973;Howorth and Vucetich 1976). During the sinking of bridge piles to carry sewerage pipes across the Waikato River at Te Rapa, Hamilton (N56j754530) , peat samples were collected from about 25 m below the bed of the river within a sequence of alluvial volcaniclastic silts, sands and gravels, correlated with the Hinuera Formation and presumed to represent mainly Hinuera-l sediments.…”
Section: Cambrit!ge (Fig 3b)mentioning
confidence: 99%